Disseminating Lacan - Pettigrew, David; Raffoul, François (SUNY series in contemporary continental philosophy, 1996)
Keywords: Lacan, Jacques, 1901-1981; Lacan, Jacques, 1901-1981; Psychoanalytic Theory; Psychoanalytic Interpretation; dept.phi; faculty_collection

Saying, singing, or semiotics: "Prima la musica e poi le Parole" revisited - Marsoobian, A.T. (Journal of Aesthetics and Art Criticism, 1996)
Keywords: dept.phi

The computer revolution and the problem of global ethics - Gorniak-Kocikowska, Krystyna (Science and Engineering Ethics, 1996)
The author agrees with James Moor that computer technology, because it is 'logically malleable', is bringing about a genuine social revolution. Moor compares the computer revolution to the 'industrial revolution' of the late 18th and the 19th centuries; but it is argued here that a better comparison is with the 'printing press revolution' that occurred two centuries before that. Just as the major ethical theories of Bentham and Kant were developed in response to the printing press revolution, so a new ethical theory is likely to emerge from computer ethics in response to the computer revolution. The newly emerging field of information ethics, therefore, is much more important than even its founders and advocates believe.
Keywords: Computer ethics; Computer revolution; Global ethics; Industrial revolution; Printing revolution; Professional ethics; dept.phi